Development of Activity of Daily Living Program for Parents with Autistic Children in Surabaya - Dita Utami Febriani (Department of Special Education, 2017)
The result of observation in some parents shows that there is no guidance used by parents in the implementation of self-study, washing hands, eating, and drinking, so that, it can inhibit parents in providing treatment for autistic children at home. To assist parents in understanding the ways of teaching for eating, drinking and hand-washing activities, the researcher develops the Activity Daily of Living Program. This research is generally aimed at developing the ‘Activity of Daily Living’ program for parents to improve the ability of children with autism. The specific objectives are: (a) Produce a product development of activity of daily living program for the parents to improve self-help ability of children with autism, (b) Describe the feasibility of product development of activity of daily living program for parents to improve autistic children’s self-help ability. This research used a development approach by adapting the development model of Borg and Gall (2007). This development process consists of 10 development steps. This research activity was conducted limited trials of six parents (as users) in Surabaya. Feasibility results according to percentage of material experts obtained 76.19%, media / design experts with 77.77% percentage, and users (parents earn 77.77%), so that, it can be categorized into good. The result of this development is activity of daily living program which is packed in A4 paper size, 150 paper thickness, art paper type and 41 pages in which there are some steps of activity accompanied by picture in doing activity sch as hand washing, eating.Hasil observasi dibeberapa orang tua menunjukkan selama ini belum ada pedoman yang digunakan oleh orang tua dalam pelaksanaan pembelajaran bina diri seperti mencuci tangan, makan, dan minum sehingga dapat menghambat orang tua dalam memberikan penanganan kepada anak autis dirumah. Untuk membantu orang tua dalam memahami cara-cara mengajarkan kegiatan makan, minum dan mencuci tangan peneliti mengembangkan program activity daily of living. Penelitian ini secara umum bertujuan mengembangkan program activity of daily living bagi orang tua untuk meningkatkan kemampuan anak autis. Tujuan khususnya, (a) menghasilkan produk pengembangan program activity of daily living bagi orang tua untuk meningkatkan kemampuan bina diri anak autis, (b) mendeskripsikan kelayakan tentang produk pengembangan program activity of daily livingbagi orang tua untuk meningkatkan kemampuan bina diri anak autis. Penelitian ini menggunakan pendekatan pengembangan dengan mengadaptasi model pengembangan Borg and Gall (2007), Proses pengembangan ini terdiri dari 10 langkah pengembangan. Kegiatan penelitian ini dilaksanakan uji coba terbatas terhadap enam orang tua (sebagai pengguna) di Surabaya. Hasil kelayakan menurut ahli materi prosentase yang diperoleh 76,19%, ahli media/desain dengan presentase 77,77% , dan pengguna (orang tua memperoleh 77,77%) di lapangan dapat dikategorikan baik/layak. Produk yang dihasilkan dari pengembangan ini yaitu program activity of daily livingyang dikemas dengan ukuran kertas A4, tebal kertas 150, jenis kertas art paper dan jumlah halaman 41halaman yang didalamnya terdapat langkah-langkah kegiatan aktivitas yang disertai gambar dalam melakukan aktivitas seperti mencuci tangan,makan.DOI: http://dx.doi.org/10.17977/um029v4i12017p075